Whole exome sequencing identifies a new DPY19L2 variant c.1232_1233insA in Tunisian infertile patient with globozoospermia - Wiem Ayed; Nicolas Thierry-Mieg; Wajh Hammami; Meriem Ben Khalifa; Sonia Mnallah; Hanène Eloumi; Amel Zhioua; Anis Chaker; Fethi Zhioua; Pierre F. Ray; Ahlem Amouri (Middle East Fertility Society Journal)
Abstract Background Globozoospermia is a rare male infertility disorder characterized by the presence in the ejaculate of round-headed sperm cells lacking an acrosome, a crucial structure for fertilization. While genetic factors play a significant role in the etiology of this condition, the precise mechanisms remain elusive. Recent studies have identified mutations in the DPY19L2 gene as a major cause of globozoospermia. This gene encodes a protein involved in the development and maturation of sperm cells, particularly the acrosome biogenesis. Mutations in DPY19L2 disrupt this process, leading to the production of abnormal sperm cells. However, DPY19L2 mutations account for only a subset of globozoospermia cases, suggesting the involvement of other genetic factors. Patients and methods Eighteen infertile men with total and partial globozoospermia were investigated. For all patients, screening of DPY19L2 total deletions was carried out by a qualitative PCR. When a positive diagnosis was not obtained (absence of a homozygous deletion), WES was conducted. Results Total deletion of DPY19L2 was found in 33% of all patients and in 60% of total globozoospermic ones. WES conducted in only two patients identified a novel DPY19L2 frameshift mutation (c.1232_1233insA) p.Arg412GlufsTer3 in one patient with total globozoospermia. The pathogenesis of this new variant is supported by In Silico prediction tools and by its absence in control patients and different published databases. Conclusions We confirm here the large implication of DPY19L2 in Globozoospermia, and we enrich the gene spectral mutation. Identification of the genetic basis of globozoospermia is crucial for accurate diagnosis, genetic counseling, and the development of potential therapeutic interventions.